O processo (auto)formativo em narrativas docentes: da metamorfose no ensino à recomposição da aprendizagem docente - Costa, Gabriela Santana da (2024)
This research focuses on the in-service training of teachers in the face of a scenario of transformations and changes at school, which occurred during the Covid-19 pandemic period, between 2020 and 2023. When the pandemic emerged, it brought with it a series of changes that affected several fields, including education and teaching. As a teacher, I understand the need to discuss this scenario in which we were inserted and which, consequently, reflected in the construction of a self-training process for educators at that time. We emphasize that we will make a temporal cut of this period, despite its impacts on teacher training, the object of this research, will reverberate for many years. The main objective of the research is to investigate teacher training in the context of a school metamorphosis (Nóvoa,2022) perceived during the pandemic scenario through teachers' narratives, reflecting on their learning recomposition. We also present that this research is qualitative, as it is based on the interpretation, comparison and description of the experience, so we chose to work with the narratives, exploring their meanings and meanings in relation to this teaching (re)construction. Within this narrative perspective, we will use reflection on the hero's journey (Campbell, 2008) where we understand that the figure of this teacher goes through a path of stages and confrontations that support our reflective discussion towards our objectives. As results perceived in this research, we highlight the (re)construction of the teaching identity of educators who see themselves as part of a transformation, understood as a school metamorphosis where, based on what we analyze and investigate, we understand it as a recomposition of teaching learning and which happens from a (self)formative process. To this end, we built as an educational product, a professional training course entitled “The (self) formative process in teaching narratives: from the metamorphosis of teaching to the recomposition of teaching learning” and which aims to enable teaching protagonism within the construction for its own sake. self-formative process and who acted during the pandemic context.